ANALISIS SINERGITAS POLISI MILITER ANGKATAN LAUT DAN KEPOLISIAN REPUBLIK INDONESIA DALAM TATARAN KEWENANGAN PENANGANAN PERKARA YANG MELIBATKAN PNS DI LINGKUNGAN TNI ANGKATAN LAUT - Risal, Andi (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2021)
This research focuses on solving problems in the field of law in the Indonesian Navy which regulates the mechanism for the synergy between the Pomal and the National Police regarding the delegation of criminal cases carried out by civil servants within the Navy, the mechanism for carrying out investigations and investigations carried out by investigators and Pomal investigators or Provos Unit against the process of examining civil servants with civilian status, technical rules within the Indonesian Navy that regulate legal settlement if there is a difference of opinion between Pomal and Atkum investigators regarding the settlement of cases carried out by civil servants in military units. The research method used is a legal research method with a descriptive approach. Synergy and cooperation in the use of software and hardware in their respective investigative fields. The process of delegating case files and resolving criminal cases involving civil servants within the Navy can run well and smoothly due to a good cooperative relationship and synergy between Pomal investigators and Polri investigators. The process of resolving disciplinary violations committed by civil servants within the Indonesian Navy is carried out by Pomal investigators starting from examining violations, preparing for administrative completeness of examinations to imposing disciplinary penalties by officials authorized to punish within the Navy.